2015
DOI: 10.1039/c5ra13171e
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of Bi2S3 nanowires on BiVO4 nanostructures for enhancing photoelectrochemical performance

Abstract: In this paper, a novel Bi 2 S 3 /BiVO 4 heterojunction film was prepared by a facile drop-casting and hydrothermal method for the first time. The as-prepared films were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM) and ultraviolet visible spectrometry (UV-Vis). Interestingly, the heterojunction film was formed by epitaxial growth of Bi 2 S 3 nanowires on BiVO 4 nanostructures and exhibited a good visible light absorption performance. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 47 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…In addition, on account of its highly anisotropic layer structure, Bi 2 S 3 tends to form 1D nanowire or nanorod nanostructure [53][54][55]. In our previous works, Bi 2 S 3 NWs were synthesized from the BiVO 4 via a simple hydrothermal process and the prepared films show an excellent PEC hydrogen generation performance [53]. It is very attractive and desirable to design and develop a novel 1D/1D heterogeneous architecture of Bi 2 S 3 /TiO 2 nanostructrure because such a nano-composite structure is expected to have better charge transport rate, light absorption and larger surface areas [56,57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, on account of its highly anisotropic layer structure, Bi 2 S 3 tends to form 1D nanowire or nanorod nanostructure [53][54][55]. In our previous works, Bi 2 S 3 NWs were synthesized from the BiVO 4 via a simple hydrothermal process and the prepared films show an excellent PEC hydrogen generation performance [53]. It is very attractive and desirable to design and develop a novel 1D/1D heterogeneous architecture of Bi 2 S 3 /TiO 2 nanostructrure because such a nano-composite structure is expected to have better charge transport rate, light absorption and larger surface areas [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…1D TiO 2 NRs grown directly on a transparent conductive substrate is considered as a desirable nanostructure for the PEC cells, because of its large specific surface, high electron transport rate and easy synthesis [32,52]. In addition, on account of its highly anisotropic layer structure, Bi 2 S 3 tends to form 1D nanowire or nanorod nanostructure [53][54][55]. In our previous works, Bi 2 S 3 NWs were synthesized from the BiVO 4 via a simple hydrothermal process and the prepared films show an excellent PEC hydrogen generation performance [53].…”
Section: Introductionmentioning
confidence: 99%
“…Third, Bi 2 S 3 /WO 3 films can be obtained from hydrothermal the BiVO 4 /WO 3 films. BiVO 4 can react with thiourea (CN 2 H 4 S) to form Bi 2 S 3 in the hydrothermal process, which has been reported in the in our previous work [52]. Due to the high anisotropy of Bi 2 S 3 , the Bi 2 S 3 nanobelts with layer structure will be selectively formed on the WO 3 nanoplate [52e55].…”
Section: Resultsmentioning
confidence: 93%
“…As can be seen, the MS slope of BiVO 4 /WO 3 electrode was greater than that of Bi 2 S 3 /WO 3 electrode, indicating a higher charge carrier density in the Bi 2 S 3 /WO 3 electrode. Moreover, it was found that coupling with Bi 2 S 3 shifted the flat band potential to the negative direction from 2.45 V to 0.09 V. The negative shift of flat band potential implies a larger accumulation of electrons in the coupled heterostructure and reduced recombination of the electron and hole [32,52,62]. To better understand how our cell works, the schematic diagram of the cell is shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation